A (In)sustentabilidade do discurso do desenvolvimento sustentável - Moreira, Luciano Accioly Lemos (2010)
This paper is an analysis about discourse of sustainability contained in some projects drawn up by the UN/World Bank and UNESCO. We thus unveil the ' new ' and ' old ' senses agitated by sustainability which resets the continuous functioning of the capital on the countries, and poor people. We analyze our object through theoretical and methodological bases of French discourse analysis based mainly in Pêcheux, and reflections about language, speech and ideology in Marx, Leontiev and Lukács. In our study, we try to capture the effect of senses movement mobilized by discursive event of sustainability. This configures itself in a reply ideological effects of structural crisis current capital, which must ensure and maintain the existing system metabolic and social order. The discourse of sustainability in terms of the proposed international bodies speak by "everyone", and to "everyone", in an world without conflicts of classes". However, the sustainability of wealth, poverty, addiction, subordination, inequality, violence, unemployment, debt levels supportable for reproduction of this system, mobilizes/stirs the senses, causing an effect in which under a "new" appearance remains the "old", preserves the capital. Nature and human life, under the domain and control of project sustainability, remain threatened with extinction because of human action and led to the logic of the capitalist system. The impossibility of effective sustainability in this society governed by destructive imperatives of structural capital exposes the limits of the current system, and we take another tack radically distinct from the project in question. Sustainability will only be possible in an economic system beyond the capital, that means, the communism. The production and reproduction of life must be guided by the foundation work by associated and free workers. Only in this way, the relationship between man and nature can be realized by using a world social planning, in a way conscious and humanitarian.